PENGARUH PELAJARAN AQIDAH AKHLAQ TERHADAP PERILAKU KEAGAMAAN SISWA - Subekti, M. Yusuf Agung Subekti (TA'LIMUNA: Jurnal Pendidikan Islam, 2012)
The rapid progress in various area recently is not guarantee peacefulness and calmness in human life, if there is not attention in value and the norms of humanity. In this case religion represent the single the place of capable to execute the target of human life perfectly. But, ironically, that modern man now inclined leave religion and exactly run after world items, so that is not impossible if the problems of life is more complex. Do not get out of the problematical is problem decline of moral which do not only befall young people, but oppositely also exactly flatten entire all human being.There are some problems formulation which later will be made by solution object in this writing. They are: 1) How execution lesson of aqidah akhlak in MTsN Selorejo. 2) What values which implied in lesson of aqidah akhlaq in MTsN Selorejo. 3) How influence lesson of aqidah akhlaq to religious behavior of student in MTsN Selorejo. From this problem formualation in expecting to reach target which consist of: Knowledge about execution lesson of aqidah ahlaq in MTsN Selorejo the which is consist in it and also influence to religious behavior of student in MTsN Selorejo.